Moral Governance and Discipline in Hybrid Tahfidh Pesantren: A Study of Millennial Qur’an Memorizers at School and Pesantren - Zaenurrosyid, Ahmad; Sholihah, Hidayatus (Santri: Journal of Pesantren and Fiqh Sosial, 2025)
The integration of schools and pesantren has become a rapidly growing educational model in Indonesia, particularly in shaping the millennial generation of Qur’an memorizers (hafidh). This model combines the formal school curantriculum with a pesantren system based on Qur’anic memorization (tahfidh). However, in practice, various challenges arise concerning regulations, violations, and the forms of punishment applied to santri (student). These regulations serve to maintain santri discipline, academic policies, and character development. Despite well-established regulations, violations frequently occur among millennial santri, both in academic contexts and pesantren discipline. This study employs a qualitative approach with a case study design. The findings indicate that regulations within this integrated model cover academic discipline, pesantren ethics, and Qur’an memorization obligations. Common violations include negligence in memorization targets, improper use of technology, and absenteeism from pesantren activities. The forms of punishment applied range from verbal warnings and social sanctions to special guidance for improving discipline. These findings provide insights for educational institutions in formulating more effective policies to nurture millennial santri to excel in both formal education and Qur’anic memorization.